2008
DOI: 10.1007/s10695-008-9290-6
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses to starvation in the European eel (Anguilla anguilla): effects on haematological, biochemical, non-specific immune parameters and skin structures

Abstract: The physiological effects of short-term starvation on some haematological, biochemical and non-specific immune response parameters together with the histological structure of the skin, were investigated in the European eel, Anguilla anguilla. Blood haemoglobin and haematocrit, serum glucose and cortisol, hemolysins, haemagglutinins, and lysozyme in the plasma, kidney and epidermal extract, were measured in fish after 31, 42 and 58 days of starvation, and compared to those of fed fish. Starvation did not affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
65
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 79 publications
11
65
1
Order By: Relevance
“…Additionally, plasma lysozyme activity significantly diminished in the 2-week starvation group. Similarly, Caruso et al (2010Caruso et al ( , 2011 found a significant decrease in the plasma lysozyme activity of European eel and blackspot sea bream (Pagellus bogarave) after 31 days starvation. One the other hand, no effect of starvation periods has been detected in lysozyme activity of European sea bass (Dicentrarchus labrax) and red porgy (Caruso et al 2011(Caruso et al , 2012.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Additionally, plasma lysozyme activity significantly diminished in the 2-week starvation group. Similarly, Caruso et al (2010Caruso et al ( , 2011 found a significant decrease in the plasma lysozyme activity of European eel and blackspot sea bream (Pagellus bogarave) after 31 days starvation. One the other hand, no effect of starvation periods has been detected in lysozyme activity of European sea bass (Dicentrarchus labrax) and red porgy (Caruso et al 2011(Caruso et al , 2012.…”
Section: Discussionmentioning
confidence: 85%
“…One the other hand, no effect of starvation periods has been detected in lysozyme activity of European sea bass (Dicentrarchus labrax) and red porgy (Caruso et al 2011(Caruso et al , 2012. Moreover, starvation for 42 and 58 days did not significantly affect the lysozyme activity of European eel (Caruso et al 2010). Apparently, the influence of fasting on fish lysozyme activity could vary by the duration of starvation and fish species.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations